Pergeseran Fungsi Jaksa Sebagai Dominus Litis Ke Arah Restorative Justice: Analisis Normatif Dan Empiris - Kurdi, Kurdi; Mazjah, Ibnu; Dadek, Teuku Ahmad (Universitas Medan Area, 2025)
The Indonesian criminal justice system is undergoing a fundamental transformation from a retributive approach to restorative justice. This study aims to analyze the implications of this paradigm shift on the dominus litis principle upheld by the Prosecutor's Office, and evaluate its implementation in ensuring legal certainty and justice for victims. The research method used is socio-legal, combining normative analysis of laws and regulations (Criminal Procedure Code, Prosecutor's Office Law, New Criminal Code, Perja 15/2020) with empirical analysis related to the reality of law enforcement. The results of the study indicate that restorative justice does not weaken the dominus litis principle, but rather functionalizes it into a more humane discretionary authority, changing the role of prosecutors from mere prosecutors to peace facilitators. However, empirically, weaknesses were found in the legal product of the Decree on Termination of Prosecution (SKPP), which is purely administrative in nature, making it vulnerable to pretrial and weak in the execution of compensation for victims. This study concludes that to ensure complete legal certainty without compromising victims' rights, the implementation of restorative justice must be synchronized with Article 132 of Law No. 1 of 2023 (New Criminal Code) and adopt a judicial scrutiny mechanism to ensure that peace agreements have binding enforcement power.